Evaluation of exotic and South African isolates of Beauveria bassiana as potential mycoacaricides of Tetranychus urticae Koch - Bhana, Nainisha Morar (My University, 2008)
Economic losses caused by the two spotted spider mite (Tetranychus urticae Koch) in the agricultural industry prompted the initiation of this project to evaluate the potential of native and exotic Beauveria bassiana isolates as biocontrol agents against this pest. Before the selection of a potential mycopesticide for use at a commercial scale, several crucial criteria must be taken into consideration. The application of some of these criteria have been the focus of this study and include: production of virulent B. bassiana inoculum, an evaluation of the virulence of the fungus against T. urticae, monitoring of the fungal infection cycle in T. urticae and establishing a phylogenetic evaluation of B. bassiana isolates using rDNA sequence analysis. A two-stage in vitro diphasic fermentation process produced B. bassiana inoculum. In the first submerged phase the impact of nutrient treatments (carbon and nitrogen) at different concentrations (3% and 4%) in a 1:1 ratio was investigated for mycelium dry mass production and spore yield. The 4% nutrient concentration yielded a higher mycelium dry mass yield compared to the 3% and was therefore used in the second semi-solid phase to stimulate aerial conidia formation in response to low nutrient stress. The fungal structures produced during the first phase of the diphasic fermentation process were submerged conidia recognized as small, spherical structures with a smooth form. In comparison, inoculum of the second semi-solid phase produced aerial conidia with small, spherical, rough surfaces and a brittle appearance assumed to be related to nutrient deprivation. Nutritional parameters exploited in this study favoured conidia production for use as a potential mycopesticide. An in vitro bioassay compared the infectivity of exotic and native isolates of B. bassiana against T. urticae adults. All the isolates were pathogenic with mite mortality increasing over time. Differences in the virulence of the B. bassiana isolates were demonstrated suggesting host-specificity. With respect to the native isolates B. bassiana (PPRI 04305) was more virulent than the B. bassiana sensu latu isolates (PPRI 04304 and PPRI 04306). The differences in the virulence of the native isolates are reflections of genetic differences demonstrated in the phylogenetic analyses in this study. The results of the preliminary bioassay study suggest that B. bassiana has the potential as a biocontrol agent of T. urticae. Microscopy was used to morphologically visualise the post infection cycle of a native B. bassiana isolate (PPRI 04305) in the two-spotted spider mite. The infection cycle observed in the current study is in agreement with those described in a number of agricultural pests. However, aspects not observed before with T. urticae infection included limited hyphal growth on the cuticle surface before penetration, per os mode of entry, cuticular melanization, lateral hyphal development under the cuticle and aerial hyphal emergence through the setal annulum on the dorsal surface of the cadaver. These observations will stimulate further research in the development of B. bassiana as a mycoacaricide. rDNA analysis of the ITS1-5.8S-ITS2 regions of different Beauveria species was assessed for strain genotyping and population studies. Fitch parsimony and neighbour joining analyses displayed species differentiation and confirmed that B. bassiana was not a monophyletic group but a species complex. Distinct clades in the phylogenetic analyses in the current study were matched to four species of Beauveria: B. bassiana, B. cf. bassiana, Beauveria brongniartii and Beauveria caledonica species. Two South African isolates PPRI 04304 and PPRI 04306 morphologically assigned to B. bassiana, are assumed to be either B. caledonica or a close relative of B. caledonica based on the rDNA analysis. However, due to the lack of confirmation of the change of species identification of these native isolates, they are regarded as B. bassiana sensu latu. Results from this study demonstrated the importance of rDNA analysis in biocontrol studies for population studies and species differentiation. The material in this dissertation highlighted some important characteristics relevant for the biocontrol of T. urticae by B. bassiana. Aerial conidia produced by the cost-effective diphasic fermentation process were virulent against T. urticae and demonstrated high percentage mortalities. B. bassiana was shown to be a generalist pathogen with strain-dependent differences in nutrient preferences and virulence against the mite. Differences in the infectivity of the native isolates B. bassiana (PPRI 04305) and B. bassiana sensu latu (PPRI 04304 and PPRI 04306) were reflections of the genotypic separation of the isolates demonstrated by rDNA analysis. The results obtained from this research project are promising for the ongoing research and development of Beauveria isolates as efficient mycoacaricides against T. urticae for the South African agricultural market.
Keywords: Beauveria bassiana; Tetranychus urticae; biocontrol